(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Marine renewable energy (MRE) development faces many challenges. Uncertainty from the regulatory community regarding environmental effects can often result in project delays and costly monitoring campaigns. Additionally, effectively studying organisms in dynamic and variable conditions is difficult under normal circumstances; high-energy environments like tidal streams and channels add to this difficulty. Common means of surveying and monitoring marine habitats and species for environmental impact assessments for MRE projects include active and passive gear types and approaches. Traditional active sampling methods include bottom and pelagic trawls, nets and grabs, whereas passive sampling can include non-invasive underwater visual surveys or acoustic sonars. While the latter rarely provides truly reliable identifications to the species level, the former comes with the inherent drawback of killing most of the catch. These traditional tools and approaches for monitoring the potential effects of MRE technologies are often insufficient or challenging to implement around tidal turbines due to the strong currents, limited visibility, and short slack windows between ebbs and flows. The analysis of environmental DNA (eDNA) is a relatively new method that uses molecular techniques to detect and identify species from genetic material shed in their environment. This material is collected through water samples and does not require the physical capture or handling of any organisms. A recent project in a tidal channel in Washington State (U.S.) showed that eDNA is a cost-effective, comprehensive, and reliable alternative to conventional methods for evaluating fish presence and habitat use in the context of tidal energy development. The project team developed an understanding of temporal and environmental factors that may affect fish eDNA data throughout seasons and tidal cycles. A follow-up project is now looking at establishing the efficacy of eDNA in the same high-energy environment by quantifying the effects of hydrodynamic and seasonal variation on molecular response variables, validating eDNA results using underwater images, and evaluating the relevance of findings to the regulatory context for MRE monitoring programs. The project especially relies on twelve consecutive months of eDNA samples and underwater images collection. This paper will present an overview of the relevance of the eDNA approach to the U.S. regulatory context for fish monitoring around tidal energy projects, as well as preliminary results of the field campaign. With optimized sampling designs, molecular monitoring approaches will become a common robust and affordable tool for assessments at MRE sites to identify whether changes in presence and habitat use occur, which is particularly valuable for threatened or endangered species.